2022
DOI: 10.3389/fpls.2022.979585
|View full text |Cite
|
Sign up to set email alerts
|

Advanced genes expression pattern greatly contributes to divergence in Verticillium wilt resistance between Gossypium barbadense and Gossupium hirsutum

Abstract: Verticillium, representing one of the world’s major pathogens, causes Verticillium wilt in important woody species, ornamentals, agricultural, etc., consequently resulting in a serious decline in production and quality, especially in cotton. Gossupium hirutum and Gossypium barbadense are two kinds of widely cultivated cotton species that suffer from Verticillium wilt, while G. barbadense has much higher resistance toward it than G. hirsutum. However, the molecular mechanism regarding their divergence in Vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In G. barbadense, GBGT64_2 and GBGT64_4 may participate in the response to FOV treatment. Furthermore, utilizing transcriptome data [34], we observed that in G. hirsutum, the MEturquoise module was signi cantly positively correlated with post-inoculation at 144 h, while in G. barbadense, the MEturquoise module was signi cantly positively correlated with post-inoculation at 72 h. This may suggest that GHGT64_4 initiated immune response to Verticillium wilt earlier in G. barbadense compared to G. hirsutum.…”
Section: Investigation Into Expression Pro Les Of Gt64 Gene Family Me...mentioning
confidence: 82%
See 2 more Smart Citations
“…In G. barbadense, GBGT64_2 and GBGT64_4 may participate in the response to FOV treatment. Furthermore, utilizing transcriptome data [34], we observed that in G. hirsutum, the MEturquoise module was signi cantly positively correlated with post-inoculation at 144 h, while in G. barbadense, the MEturquoise module was signi cantly positively correlated with post-inoculation at 72 h. This may suggest that GHGT64_4 initiated immune response to Verticillium wilt earlier in G. barbadense compared to G. hirsutum.…”
Section: Investigation Into Expression Pro Les Of Gt64 Gene Family Me...mentioning
confidence: 82%
“…Transcription analysis GHGT64_4 between G. hirsutum and G. barbadense Although a series of bioinformatics analyses have been conducted on the GT64 gene family and we have gained a basic understanding, their potential role in resistance to Verticillium wilt in upland and island cotton is still unclear. Based on the transcriptome data of 90 published samples [34] (derived from TM-1 and Hai7124 at time points 0 h, 12 h, 24 h, 48 h, 72 h, 96 h, 120 h, 144 h pre-and post-inoculation). TM-1 is a variety with low susceptibility to the disease, while Hai7124 is disease-resistant.…”
Section: Validation Of Ghgt64_4 In Cottonmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data converted from the Illumina platform was subjected to quality control before subsequent analysis. The transcriptome analysis method was as described previously (He et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This susceptibility leads to a substantial reduction in both fiber quality and yield 14 . Notably, G. barbadense demonstrates high resistance or immunity to cotton V. dahliae , making it a valuable resource for identifying key genes associated with Verticillium wilt resistance and uncovering the corresponding regulatory mechanisms 15 , 16 . However, the lack of V. dahliae -susceptible G. barbadense germplasm resources has limited the research focus to comparing V. dahliae- resistant G. barbadense with either V. dahliae -resistant G. hirsutum or V. dahliae -susceptible G. hirsutum varieties 17 22 .…”
Section: Background and Summarymentioning
confidence: 99%